GW24-e3065 Risk Factors for Recurrence of Cardiovascular Events Following Acute Coronary Syndrome: Longitudinal Analysis from 2006 to 2011. (1st October 2013) - Vanessa, S Reddy; Luthra, Rakesh; Xu, Yaping; Fisher, Maxine; Power, Thomas; Wilhelm, Ken; Cziraky, Mark
Abstract : Objectives: Cardiovascular (CV) disease is the leading cause of mortality in the US and worldwide; thus, it is important to understand the disease sequelae and prognostic predictors to help improve patient outcomes and reduce healthcare costs. Methods: Hospitalised patients with an ICD-9 code consistent with the diagnosis of acute coronary syndrome (ACS) were identified from the HealthCore Integrated Research Database (HIRD SM ) between January 2006 and September 2011. A multivariable Cox proportional hazards model was used to evaluate the effect of risk factors on time to first subsequent CV event (defined as stroke, myocardial infarction or coronary heart disease-related mortality), adjusting for baseline demographic characteristics, comorbidities, treatment utilisation and index ACS characteristics. Results: Of 140, 903 ACS patients identified, mean age was 66.8 years, 58.6% were male, and mean follow-up was 1.9 years. Baseline comorbidities include 41.9% with type 1 or 2 diabetes mellitus (DM), 60.4% hypertension (HTN), 10.7% renal dysfunction and 3.3% prior CABG/PCI. During the index ACS hospitalisation, 42.7% had unstable angina, 40.3% CABG and/or PCI and 3.6% of patients died. A total of 22.0% of patients had a recurrent CV event following index ACS, with an increased adjusted hazard of a recurrent event if the patient was older (hazard ratio [HR] = 1.48 in > 65 versus < 65 years), had a history of heart failure (HR = 1.41), renal dysfunction (HR = 1.36), HTN (HR = 1.14) or DM (HR = 1.10), all P < 0.001. Additionally, patients had a decreased adjusted hazard of a recurrent CV event with pre-admission single or fixed-dose combination statin use (HR = 0.96 and 0.87, respectively) or a CABG prior to admission (HR = 0.89), all P < 0.001. Conclusions: Following an ACS event, patients with pre-admission statin use or a prior CABG had decreased risk, while older patients or those with baseline comorbidities had increased risk of an adverse CV event occurring sooner. Ultimately, identifying high-risk ACS subgroups may facilitate tailored and more aggressive treatment to improve outcomes.